1986
DOI: 10.1093/infdis/154.3.471
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Activation, Deactivation, and Probable Autooxidative Damage as a Mechanism of Neutrophil Locomotory Defect in Trauma

Abstract: We studied 46 patients who suffered from serious blunt trauma to examine the possible mechanism of their acquired neutrophil (PMN) locomotory dysfunction. Concentrations of plasma C3adesArg were higher in patients than in controls (310 +/- 190 ng/ml vs. 90 +/- 28 ng/ml, respectively; P = 3 X 10(-5)). Both resting and phagocytosing PMNs from the patients produced higher quantities of H2O2 (0.31 +/- 0.29 and 5.2 +/- 3.4 nmol/10(6) PMNs per hr, respectively). These levels resemble the H2O2 production of normal PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…However, recent studies by Brown et al [76] suggest that the stability of the primed state is also important, and priming stabilization factors play a role in modulating the priming response in vivo. Primed PMN have been detected in blood samples from patients with sepsis [75,77], trauma [78][79][80], and myeloproliferative disorders [81]. In addition, Zimmerli et al [68] and Folin et al [72] reported that exudate human PMNs were also primed.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies by Brown et al [76] suggest that the stability of the primed state is also important, and priming stabilization factors play a role in modulating the priming response in vivo. Primed PMN have been detected in blood samples from patients with sepsis [75,77], trauma [78][79][80], and myeloproliferative disorders [81]. In addition, Zimmerli et al [68] and Folin et al [72] reported that exudate human PMNs were also primed.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of altered oxygen tensions in regulating PMN function is well established and has been implicated in ischaemia/ reperfusion injury [12,29]. Alterations in oxygen tension have been shown to effect cell adhesion and interactions with extracellular matrix [11], endotoxin tolerance [20], and macrophage cytokine elaboration [17,30]. Therefore, we designed our studies to investigate the dynamics of the modulating effect of the normoxia/ hypoxia/reoxygenation transition on the integrin-controlled sensitivity of PMN cytokine elaboration with external stimulation at the level of cell surface receptor-ligand interactions (fMLP and LPS) as well as at the post-receptor level (direct stimulation of PKC by PMA).…”
Section: Discussionmentioning
confidence: 99%
“…Superoxide anion released by PMN was assayed by quantitative reduction of cytochrome c as described [17]. After 100 M cytochrome c in 1 ml total volume were added, PMN at 2 2 10 6 /ml in normoxic, hypoxaemic or H/R buffers (70% O 2 saturation) were adhered to buffer, Fn or Ln (1 g) for 30 min.…”
Section: Superoxide Anion Productionmentioning
confidence: 99%
“…Recent but ongoing research mainly focuses on the molecular events of ROS interacting either with pathogens or with host tissues at sites of inflammation. Surprisingly, little attention has been paid to the effect of reactive metabolites on the phagocytic cell itself (Maderazo et al, 1986). This is surprising since it is apparent that the activated phagocyte is directly exposed to its own toxic metabolites, thereby altering viability and cell function.…”
Section: Introductionmentioning
confidence: 99%